Functional Characterization of a 2OGD Involved in Abietane-Type Diterpenoids Biosynthetic Pathway in Salvia miltiorrhiza - Hu, Zhimin; Ren, Li; Bu, Junling; Liu, Xiuyu; Li, Qishuang; Guo, Wending; Ma, Ying; Wang, Jian; Chen, Tong; Wang, Ling; Jin, Baolong; Tang, Jinfu; et al. (Frontiers in Plant Science, 2022)
Salvia miltiorrhiza is one of the most commonly used Chinese medicinal herbs. Tanshinones, the most abundant lipo-soluble bioactive constituents of S. miltiorrhiza, are a class of structural highly oxidized abietane-type diterpenoids with multiple pharmacological activities. Although several enzymes including diterpene synthase, cytochrome P450, and Fe(II)/2-oxoglutarate-dependent dioxygenase (2OGD) have been functionally characterized in biosynthesis of abietane-type diterpenoids, the highly oxidized structure and complex secondary metabolic networks of tanshinones imply that more oxidases should be characterized. Here, we identified a new 2OGD (Sm2OGD25) from S. miltiorrhiza. Molecular cloning and functional studies in vitro showed that Sm2OGD25 could catalyze the hydroxylation of sugiol at C-15 and C-16 positions to produce hypargenin B and crossogumerin C, respectively. The phylogenetic analysis of the DOXC family demonstrated that Sm2OGD25 belongs to the DOXC54 clade. Furthermore, structural modeling and site-directed mutagenesis characterization revealed the importance of the hydrogen-bonding residue Y339 and the hydrophobic residues (V122, F129, A144, A208, F303 and L344) in substrate binding and enzyme activity. This work will promote further studies on the catalytic characterization of plant 2OGDs and the secondary metabolic biosynthesis network of diterpenoids.